What little boys are made of / Loving Who They Are and Who They Will Become - Daly, Jim. (Eugene, Or. : Harvest House Publishers, 2000)
Mischief dons blue jeans and totes a fishing pole in Jim Daly's Americana artwork featured throughout this unforgettable exploration of boyhood. Sweet writings express virtues gathered like treasures along a boy's journey to manhood.
Jump headlong into the land of little boys, a place of innocence and imagination defined by the worn leather of a trusty baseball glove, the best-friend nudges of a puppy dog and the joyful splash of a favorite stream In the wonderful world of boyhood, the best kind of toys are the simple props of nature and life's most memorable moments happen among friends on a lazy summer day.
Keywords: Boys -- Poetry; Boys -- Quotations; Boys